2019
DOI: 10.1038/s41598-019-54065-6
|View full text |Cite
|
Sign up to set email alerts
|

The balance between NRF2/GSH antioxidant mediated pathway and DNA repair modulates cisplatin resistance in lung cancer cells

Abstract: Lung cancer patients face a dismal prognosis mainly due to the low efficacy of current available treatments. Cisplatin is the first-line chemotherapy treatment for those patients, however, resistance to this drug is a common and yet not fully understood phenomenon. Aiming to shed new light into this puzzle, we used established normal and malignant lung cell lines displaying different sensitivity towards cisplatin treatment. We observed a negative correlation between cell viability and DNA damage induction upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 36 publications
1
63
0
Order By: Relevance
“…Recently, NRF2 activity was shown to be involved in the autophagy process [48,49] as well as mesenchymal transition and invasion in several tumors including glioblastoma [50,51]. Emerging research has demonstrated that hyperactivation of the NRF2 pathway enables protection against chemotherapeutic agents, creating an environment that favors the survival of malignant cells [19,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, NRF2 activity was shown to be involved in the autophagy process [48,49] as well as mesenchymal transition and invasion in several tumors including glioblastoma [50,51]. Emerging research has demonstrated that hyperactivation of the NRF2 pathway enables protection against chemotherapeutic agents, creating an environment that favors the survival of malignant cells [19,52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed the upregulation of NRF2 (nuclear factor, erythroid-derived 2-like 2 factor) has been observed in a wide array of tumors including breast, ovarian, prostate, skin, lung and pancreas [ 32 , 44 ]. NRF2 is a master regulator of antioxidant response as a transcription factor regulating expression of several enzymes responsible for glutathione synthesis, including glutamate-cysteine ligase modifier subunit (GCLM) and the glutamate-cysteine catalytic subunit (GCLC), as well as enzymes related to GSH utilization, such as glutathione reductase, glutathione peroxidase and glutathione S transferase (GST) [ 45 , 46 ].…”
Section: Glutathione Redox and Ros In Healthy And Tumor Cellsmentioning
confidence: 99%
“…Increased GSH has long been considered as an accomplice in the progression and multidrug resistance of cancer [122][123][124][125][126]. GSH depletion obtained by the irreversible GCL inhibitor BSO is the most commonly used method and is associated with many chemotherapy drugs.…”
Section: Modulate Ros Generation and Elimination Tomentioning
confidence: 99%